ANALISIS PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI MAKANAN DAN MINUMAN TAHUN 2013-2017 - Jasmine Putri Dewi; Esti Damayanti (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This study aims to analyze the effect of Capital Structure, Profitability and Company Size on the Value of Manufacturing Companies in the Food and Beverage Industry Sector in Indonesia. This research was conducted on annual data of manufacturing companies in the food and beverage industry in the form of DER, ROA and Ln data for the period 2013 - 2017. The results of this study indicate that partially the capital structure has a positive and significant effect on the value of manufacturing companies listed on the Stock Exchange, profitability has a significant effect on the value of manufacturing companies listed on the IDX, the size of the company has a significant effect on firm value. While simultaneously the capital structure, profitability and size of the company significantly influence the value of the company.